HISTORY OF DEVELOPMENT OF EDUCATION AND TEACHING IN AZERBAIJAN - Asadova Ayten Vagif; Leyla Aliyeva Elkhan (Unib Press, 2026)
Education and science play a fundamental role in the development of societies. Education enables individuals to acquire knowledge and skills, thereby supporting social progress and cultural development. Throughout history, the concept of education has changed according to the needs of societies and has been implemented in different forms in every period. In Azerbaijan, the tradition of education dates back to ancient times, where writing, mathematics, and religious education developed in states such as Manna, Atropatena, and Caucasian Albania. During the Middle Ages, under the influence of Islamic culture, madrasas became widespread, scientists were trained, and educational institutions were established in many cities. In the IX century, during the Russian Empire period, the education system changed and Russian-language schools became widespread. During the Azerbaijan Democratic Republic (1918–1920), national education policies were developed and the Azerbaijani language was declared the official state language. In the Soviet period, education became ideologically oriented, literacy rates increased, and higher education institutions expanded. After independence, the education system was modernized, preserving national values while aligning with European standards. Today, Azerbaijan’s education system is democratic, secular, and multicultural. Digitalization, technology, and human capital have become key elements shaping modern education and its development.